Active learning in business analytics course through educational games / Chuah Soo Cheng and Keshminder Singh Jit Singh - Chuah, Soo Cheng; Singh, Keshminder Singh Jit (Universiti Teknologi MARA, Perlis, 2020)
The challenge for business analytics course is that it requires students to revisit prior statistical knowledge and have a basic understanding of Microsoft Excel in order to master this course. Therefore, educational games have the potential to address the above-mentioned challenge since games are typically regarded as an effective tool to help learners master certain concepts and reinforce their development and skills. This paper explored the challenges faced by lecturers when engaging their students in assessments related to business analytics and how they could use educational games to promote active learning in the classroom. A mixed methods approach, by using an online survey and face-to-face semi-structured interviews with lecturers from the Faculty of Business and Management, UiTM was employed for data collection. The study thus found that the major challenges faced by lecturers included students not revising their prior learned statistical knowledge, displaying a lack of understanding of the subject matter, and weakness in decisionmaking skills. Lecturers agreed that educational games posed their potential to increase student participation in the classroom, improve their understanding, promote teamwork, and infuse creativity. Hence, this study proposes that the academics should develop educational games to proliferate active learning in the classrooms for the purpose of solving shortcomings related to the business analytics course.